Cranial fasciitis in children: clinicoradiology features and management - Yonghua Xiang; Siping He; Zhengzhen Zhou; Qing Gan; Ke Jin (BMC, 2022)
Abstract Background Cranial fasciitis (CF) is a rare benign fibroproliferative lesion of the skull. To date, the summarized radiologic characteristics and the subtype of the disease have not been reported. our purpose was to summarize the characteristic clinicoradiology features and management of CF and to improve the knowledge of radiologists and clinicians. Methods We searched our institution's database and retrieved the clinical and radiologic data of CF patients confirmed by histopathological examination. The clinicoradiology features and management of CF were analysed retrospectively. Results A total of 14 CF patients were included. A total of 85.7% of the patients presented with a painless, firm, nonmobile and single mass. Tenderness and multiple masses were found in 14.3% of the patients. The mass was clearly increased in 2 patients and gradually increased in 5 patients in the short term. We divided these patients into three types based on the CT characteristics. The characteristic features of type I (9 patients) presented as an expansive and osteolytic bone destruction with a soft tissue mass. Type II (2 patients) presented as a scalp mass with mild erosion of the outer skull plate. Type III (3 patients) presented as a scalp mass without skull destruction. All patients underwent surgical resection. For type I patients, craniectomy and cranioplasty were performed. For type II patients, complete excision of the scalp mass with local skull curettage was performed. For type III patients, complete excision of the scalp mass was performed. There were no cases of recurrence after follow-up. Conclusions CF usually presents as a painless, firm, nonmobile and single mass with a clear boundary. There are generally three types of MSCT findings: bone destruction with a soft tissue mass, a scalp mass with erosion of the skull and a scalp mass. Different management strategies should be utilized for the various types of CF.